The Emergence of Female Politicians in Local Politics in Post-Suharto Indonesia - Kurniawati Hastuti Dewi (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2015)
This dissertation addresses factors behind the rise and victory of Javanese Muslim women political leaders in direct elections since 2005, in post-Suharto Indonesia. By using gender perspectives to examine political phenomenon, it reveals that that the role of Islam, gender, and networks are decisive to their political victory. The Islamic belief on female leadership at the local level, provides a strong religious foundation for Javanese Muslim women politicians to assume political leadership. Ability to use their gender in combination with the idea and practice of Islamic piety, and to use religio-political support and male/female base networks in political campaign, is signifcant. This fndings indicates that important social changes has occurred in postSuharto Indonesia in where more Muslim women continue to take political leadership role beginning in local politics and gradually rising to national politics. In broader scope, this dissertation signifes that a new trend of Muslim women political leaders evolving in politics colors future discourse on gender, politics and Islam in Indonesia and more generally in Southeast Asia